Hydration kinetics of four quinoa (Chenopodium quinoa Willd.) varieties - Pumacahua Ramos, Augusto; Limaylla Guerrero, Katherine Milusca; Telis Romero, Javier; Lopes Filho, Jose Francisco (Revista Colombiana de Investigaciones Agroindustriales, 2016)
The effect of time, temperature and varieties were analyzed during kinetics hydration of quinoa grains and some physical properties were determined. Quinoa grain varieties Kancolla, Salcedo Inia, Blanca de Juli and Pasankalla were used in the study. The hydration was performed in triplicate with 25 g of grain immersed into a solution with 0.55% lactic acid and 0.2% SO2, three temperatures (30, 40 and 50°C) at seven time intervals from 0 to 6 hours were considered to determine moisture of the grains. Moisture data were adjusted to empiric model of Peleg and to the diffusion model based on the Fick’s second law. Effective diffusivity as well as activation energy of the water absorption was also determined. The data were submitted to analyses of variance (ANOVA) and Tukey’s means difference test at 5% probability. Models adjustments were evaluated through determination coefficient (R2) and mean quadratic error (RMSE). Physical properties of Pasankalla variety shown different values compared with white varieties. Peleg’s model constants K1 ranged from 28 to 65.8 (s/%) and K2 from 0.004 to 0.008 (1/%). The effective diffusivity ranged from 2.594 x 10-11 to 8.180 x 10-11 m2.s-1 and activation energy from 210.5 to 1648.5 kJ.k-1. Para citar este artículo Pumacahua, A., Limaylla, K., Telis, J. y Lopes, J. (2016). Hydration kinetics of four quinoa (Chenopodium quinoa Willd.) varieties. Rev. Colomb. Investig. Agroindustriales, 3(1), 23-33. DOI: http://dx.doi.org/10.23850/24220582.348